Seed technology manual of some reforestation species - Dayan, Maria P. (Maria de la Pena) 1950- (National Forestation Development Office and Ecosystems Research and Development Bureau, 1995)
A manual for topics, activities, and experiments regarding seed technology and related skills and concepts. Intended for the use of seed technology students and teachers, as well as those who are into the forestry and farming industry.